Ability and validity of three different methods of assessing upper-body strength-endurance to distinguish playing rank in professional rugby league players - Baker, D. G. (The Journal of Strength and Conditioning Research, 2009)
To date, little study has been performed to determine the importance of upper-body strength-endurance (S-E) to success in rugby league football. Furthermore, debate exists as to which type of S-E testing, absolute resistance or relative percent S-E testing, where performance is gauged with an absolute resistance in kilograms or with a set percentage of 1 repetition maximum (1RM), respectively, would garner more informative results. To this end, 3 different methods of assessing S-E (1 relative and 2 absolute S-E) were investigated to determine their effectiveness and validity for distinguishing between rugby league players of different ranking. In study 1, 26 players of similar strength, but different playing ranking, performed a bench press test with a resistance of 60% of their 1RM to determine if any differences existed between the groups in how many repetitions could be completed with the same relative percentage resistance. The fact that no significant difference existed between the groups in repetitions performed indicated that this test of relative S-E did not differentiate playing rank in rugby league. In study 2, 38 subjects performed tests with absolute resistances of 60 and 102.5 kg (bench press repetitions-to-fatigue (BP RTF) 60 and 102.5, respectively) in an effort to determine the merits of absolute S-E testing. Both tests significantly differentiated playing rank, but on the basis of how many repetitions were performed, only the BP RTF 60 could be considered a valid test of S-E. Absolute S-E testing with a moderate resistance of 60 kg appears to be a valid and effective test for discriminating playing rank in rugby league players.